Comparison Of Effective Dose Between Adult And Paediatric Ct Brain Using Dose Length Product - MS NITIKA C. PANAKKAL,; MR SUSHIL YADAV,; MS WINNIECIA DKHAR, (International Journal of Pharma and Bio Sciences, 2015)
Paediatric patients receive a higher effective dose from CT examinations if the similar exposure parameters developed for adults are used. The aim of the study was to compare the effective dose between adult and paediatric patients during CT brain examination, using the dose length product and to evaluate the level of optimization of scan protocols. Dose information was collected for 64 patients who underwent CT brain, among which 32 were adults and 32 were paediatric patients. CT scan of adult and paediatric patient was performed using standard helical adult and child protocol respectively, routinely followed at Kasturba hospital, Manipal. The dose information was collected from a monitor on control console. The effective dose was calculated by using region specific conversion factors. The result showed that the mean effective dose in the paediatric group was 3.34mSv which is higher than adult group having an effective dose of 2.04mSv. The study concluded that the scanning protocols should be further optimized in the paediatric group. This focuses the importance of developing size specific protocols.